3 - La lutte contre la méningite au Togo : une contribution à l’amélioration de la santé des autochtones à l’époque coloniale (1902–1960) ? - Kouzan Komlan, (Afrika Zamani, 2022)
When in January 2016, cerebrospinal meningitis epidemic erupted in Northern Togo and has caused several deaths; the Togolese government has to take urgent measures for its eradication. The exploitation of various documentary sources reveals that this epidemiological event is an old issue of public health that has always been faced by local people and Europeans since the colonial period. It is, for the colonizers, to ensure their health and especially that of indigenous people, which were the essential source of “development” of their colonies. The fight against meningitis disease in Togo begun with the German colonial power and was reinforced under the French administration. Arduous, it focused on the circles of Sokode and Mango, the main areas of predilection for this epidemic. On the eve of its independence, Togo could rejoice to have managed to eradicate this disease thanks to the effectiveness of modern medicine and to have improved its population health. However, demographic growth which contributed to this health struggle, was, fro 1960, both an asset and a challenge for the new leaders of independent Togo.